BATIK HOUSE SALES IN APPLICATIONS USING THE MICROSOFT VISUAL BASIC CEMPAKA 6.0 - Endra Sulistyawan; Sutarno, SKom.,MMSI Sutarno, SKom.,MMSI (Jurnal Sistem Informasi, 2010)
This scholarly work contains a simple application program on the computerized salesand inventory at the House of Batik Cempaka. The system works is by using the inputdata items that are available and the sales process, which will then automaticallystored in a database and display the output results will come out that will be receivedby the buyer or consumer as a receipt or purchase receipt and viewing of reportsrequired by the owners of these stores .The process of inputting the computerized sales and this makes data processing moreefficient and accurate and can provide information on existing inventory.The need for information is very important, especially in the business world. Theauthor hopes with the construction of this Application at Home Batik Cempaka, thenthe information about inventory and sales of goods can be presented well.